Protective effects of resveratrol against acetaminophen-induced toxicity in mice - VELİOĞLU ÖĞÜNÇ, AYLİZ; ŞENER, GÖKSEL; ÇETİNEL, ŞULE (WILEY, 2006)
This investigation elucidates the role of free radicals in acetaminophen (AA)-induced toxicity and the possible protection by resveratrol (RVT). BALB-c mice were injected with a single dose of 900 mg/kg AA to induce toxicity, while RVT administred in a dose of 30 mg/kg i.p. following AA. Mice were sacrificed 4 h after AA injection to determine serum ALT, AST and tumor necrosis factor-alpha (TNF-alpha) levels in blood, and glutathione (GSH), malondialdehyde (MDA) levels, myeloperoxidase (MPO) activity and collagen contents in liver tissues. Formation of reactive oxygen species in hepatic tissue samples was monitored by using chemiluminescence (CL) technique with luminol and lucigenin probe. ALT, AST levels and TNF-alpha were increased significantly after AA treatment, and reduced with RVT. AA caused a significant decrease in GSH levels while MDA levels and MPO activity were increased in liver tissues. On the other hand when RVT administered following AA, depletion of GSH and accumulation of MDA and neutrophil infiltration were reversed back to control. Furthermore increased luminol and lucigenin CL levels in the AA group reduced by RVT treatment. Our results implicate that AA causes oxidative damage in hepatic tissues and RVT, by its potent antioxidant effects protects the liver tissue. These data suggest that RVT may be of therapeutic use in preventing hepatic oxidative injury due to AA toxicity. (c) 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: acetaminophen; resveratrol; hepatic; glutathione; TNF-alpha; myeloperoxidase; RED WINE; OXIDATIVE STRESS; REACTIVE OXYGEN; FREE-RADICALS; PROTEIN; INJURY; HEPATOTOXICITY; GLUTATHIONE; MECHANISMS; MELATONIN